STRATEGI PENINGKATAN PEMASARAN DAN PENJUALAN PRODUK MELALUI SHOPEE & SOSIAL MEDIA - I Dewa Made Endiana; Anak Agung Bagus Rama Saputra (PROSIDING SEMINAR NASIONAL PENGABDIAN MASYARAKAT (SENEMA), 2024)
Business developments are currently growing very rapidly, MSMEs must follow advances in information technology with the aim of expanding markets and increasing sales. The advancement of information technology is through online sales. MSME players who want to build their business online can take advantage of social media. Judging from the existing reality, the ARA GIFT FLORIST store experiences very tight sales competition because it is located in the middle of the market. Apart from that, offline sales that are less effective due to limited store operating hours are also one of the causes of the decline in sales turnover at the ARA GIFT FLORIST store. As well as a lack of knowledge about digital marketing, it is difficult for the ARA GIFT FLORIST store business to develop.